itu Dampak Reklamasi Sabah di Filipina terhadap Hubungan Filipina dan Malaysia Tahun 2010 hingga 2020: Reklamasi Filipina di Sabah - Abdul, Jalloud (Universitas Djuanda Bogor, 2024)
The study aimed to identify the knowing and understanding towards the Republic of the Philippines reclamation on the Sabah. The study was undertaken by to investigate the perceived effects on the issue of the Philippines’ Reclamation on Sabah to the Philippine-Malaysia relations. The study attempted to answer the following questions: (1) perceive the effect of the Philippine reclamation on Sabah to the Philippines-Malaysia bilateral relations? (2) the Philippine reclamation on Sabah and its economic repercussions? (3) the Philippine reclamation on Sabah and its Political repercussions? The researcher made use of self-made guided questionnaire through purposive sampling method that was utilized to select samples of the respondents limiting the respondents into the data were analyze using thematic analysis. Based on the data gathered, the study shows that the effects of the Philippine reclamation on Sabah and its effects to the Philippines-Malaysia relations. In line with the statement of the problem of the study, the researchers found out from the results that the responses average weighted mean in Part II is 2.24 and on Part III is 2.34 both having a verbal interpretation of undecided, and the respondents perceived that negative repercussions on reclamation of the Philippines on Sabah and the reclamation will only increase the abnormal ties and tension between Malaysia and the Philippines. There’s a need of extension agent in the community by means of education to more understand and know what implications and effects that the Philippine reclamation Sabah has for both the Philippines and Malaysia, and the world. Keywords: Philippines - Malaysia Bilateral Relations, Philippines reclamation on Sabah, Repercussions, Sabah Disputes.